2010
DOI: 10.1007/s00299-010-0837-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aggregate size in Taxus suspension cell culture

Abstract: Plant cells grow as aggregates in suspension culture, but little is known about the dynamics of aggregation, and no routine methodology exists to measure aggregate size. In this study, we evaluate several different methods to characterize aggregate size in Taxus suspension cultures, in which aggregate diameters range from 50 μm to 2000 μm, including filtration and image analysis, and develop a novel method using a specially equipped Coulter counter system. We demonstrate the suitability of this technology to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…intracellular + extracellular: both in aqueous and PFD phases) yield of paclitaxel was obtained in PFD-degassed carrying cultures after two weeks of elicitation. Under the conditions of the current study we also observed in most of the cases higher lignan contents after two week elicitation, however, the PFD-aerated supported elicited cultures seemed to be more favourable for lignan accumulation (Tables 3, 4) likely due to generated to a higher extent than in PFD-degassed supported cultures oxidative stress which is believed to affect plant secondary metabolism (Shilpa et al 2010;Kolewe et al 2010). PFD application in the function of in situ extrahent could also contribute to the lower metabolite feedback inhibition and diminished cytotoxic metabolites accumulation in aqueous phases of the medium which seemed to be often the reason of limited secondary metabolites production (Malik et al 2013;Kolewe et al 2010).…”
Section: Lignan Accumulation In Cultures Of Atma and Kt Hairy Root LImentioning
confidence: 64%
“…intracellular + extracellular: both in aqueous and PFD phases) yield of paclitaxel was obtained in PFD-degassed carrying cultures after two weeks of elicitation. Under the conditions of the current study we also observed in most of the cases higher lignan contents after two week elicitation, however, the PFD-aerated supported elicited cultures seemed to be more favourable for lignan accumulation (Tables 3, 4) likely due to generated to a higher extent than in PFD-degassed supported cultures oxidative stress which is believed to affect plant secondary metabolism (Shilpa et al 2010;Kolewe et al 2010). PFD application in the function of in situ extrahent could also contribute to the lower metabolite feedback inhibition and diminished cytotoxic metabolites accumulation in aqueous phases of the medium which seemed to be often the reason of limited secondary metabolites production (Malik et al 2013;Kolewe et al 2010).…”
Section: Lignan Accumulation In Cultures Of Atma and Kt Hairy Root LImentioning
confidence: 64%
“…A Multisizer 3™ Coulter counter equipped with a 2000 µm aperture (Beckman Coulter, Brea, CA, USA) was used to determine total biomass dry weight based on previously published correlations (Kolewe et al 2010). For analysis, two × 2 mL samples of well-mixed culture broth (cells plus media) were taken from each flask.…”
Section: Methodsmentioning
confidence: 99%
“…For elicitation, 200 μM methyl jasmonate (MeJA) was added on day 7 post-transfer during the mid-exponential phase of growth, as described previously [34]. A Multisizer 3 ™ Coulter counter equipped with a 2,000 μm aperture (Beckman Coulter, Brea, CA) was used to measure culture aggregate size distributions, as described previously [30]. As the total aggregate volume was previously shown to correlate directly with biomass [30], this measurement was also used to determine dry weight (DW), and all DW data presented here were based on this correlation.…”
Section: Methodsmentioning
confidence: 99%
“…In Taxus suspension cultures, aggregates ranging from less than 100 μm to well over 2 mm have been observed [30]. Cells within these aggregates are subject to different microenvironments, leading to cell-cell differences in morphology [31] and metabolism [32].…”
Section: Introductionmentioning
confidence: 99%